2014
DOI: 10.5194/angeo-32-1349-2014
|View full text |Cite
|
Sign up to set email alerts
|

Thin current sheets with strong bell-shape guide field: Cluster observations and models with beams

Abstract: Abstract. We study the kinetic structure of intense ion-scale current sheets with strong electron currents and the guide field having a bell-shape profile. We consider four crossings of the Earth magnetotail current sheet by the Cluster mission in 2003. The thickness of these current sheets is about the ion inertial length and significantly smaller than the characteristic ion gyroradius. We analyze the asymmetry of the electron velocity distribution functions and show that the electron current is provided by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…Cluster observations have shown that the B y component can be significantly enhanced by local field-aligned currents (Rong et al 2012;Grigorenko et al 2013). In this case, we may observe a parabolic profile of B y ∼ 1 − (B x /B 0 ) 2 well described in theoretical models (Artemyev 2011;Mingalev et al 2012;Vasko et al 2014). However, the origin of such specific CS configuration with enhanced B y is still unknown.…”
Section: Discussionmentioning
confidence: 53%
“…Cluster observations have shown that the B y component can be significantly enhanced by local field-aligned currents (Rong et al 2012;Grigorenko et al 2013). In this case, we may observe a parabolic profile of B y ∼ 1 − (B x /B 0 ) 2 well described in theoretical models (Artemyev 2011;Mingalev et al 2012;Vasko et al 2014). However, the origin of such specific CS configuration with enhanced B y is still unknown.…”
Section: Discussionmentioning
confidence: 53%
“…Models have been developed for almost force-free CSs including an asymptotically small 2 and finite 46 B z component. It has been shown both theoretically 46 and observationally 4,46 that the plasma density is uniform in these CSs. In force-free CSs with a finite B z the density and temperature profiles cannot be set arbitrarily even in the MHD limit, since the field lines are curved and cross the entire CS.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, kinetic models of the developed force-free CSs generalised for relativistic plasmas 44 , could be useful for modelling CS instabilities in pulsar winds 21 . Recently there have been reports of in situ observations of force-free CSs in the magnetotails of Jupiter 4 and the Earth 3,46 . Similar force-free CSs are studied in detail in laboratory plasmas 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new DF (24) describes an equilibrium with nonuniform density and temperature profiles; we can show this by writing them as functions of z using Eqs. (9), (10), and (A13)-(A15) and the definitions of a 0 and b 0 , which gives…”
Section: Abraham-shrauner's Modelmentioning
confidence: 96%